ADDITIONAL BRACHIOPOD FINDINGS FROM THE LOPINGIAN SUCCESSION OF THE ALI BASHI MOUNTAINS, NW IRAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
Aim of this note is to describe additional findings of Lopingian brachiopods along the Main Valley section and at Localities 1, 3, and 4 of the Ali Bashi Mountains, N Iran. Here we provide:1) taxonomic descriptions of two newly recorded taxa, one of which is a new species, Meekella julfensis n. sp.;2) more information on the stratigraphic range of brachiopods from the Ali Bashi Mountains, which show a greater abundance and diversity in the upper part of the Julfa Formation, in the Ali Bashi Formation, and in the Boundary Clay. The newly collected faunas are characterized by miniaturization which is considered to be a response to deep water conditions in well oxygenated, but trophic resource-limited settings, and not a Lilliput-effect related to the end-Permian crisis;3) a discussion on the phylogenetic relationships between Araxathyris and Transcaucasathyris , proposing that the former may have evolved from the latter by the convergence of the dental plates to form a spondylium, that was probably a structure that functioned to optimize the muscle length in response to greater shell volumes.